2008
DOI: 10.1021/la803124m
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Interaction in Ionic Liquids: Effects of Ionic Structures and Surface Chemistry on Rheology of Silica Colloidal Dispersions

Abstract: To understand the important factors that dominate colloidal stability in ionic liquids (ILs), rheology of the dispersions of hydrophilic and hydrophobic silica nanoparticles were investigated in ILs with different ionic structures. The dispersion of hydrophilic silica nanoparticles in [BF(4)] anion-based ILs and in an IL containing a hydroxyl group, 1-(2-hydroxyethyl)-3-methylimidazolium bis(trifluoromethane sulfonyl)amide ([C(2)OHmim][NTf(2)]), showed an intriguing shear thickening response. Nonflocculation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
139
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 59 publications
8
139
0
Order By: Relevance
“…In addition, hydrophobic nanoparticles were prepared by grafting poly(MMA) chains on the particle surfaces to understand the peculiar colloidal stability. [84][85][86] The colloidal interaction was investigated using the Derjaguin-Landau-Verway-Overbeek (DLVO) theory, from which it was concluded that bare silica particles cannot be stabilized in ILs. In fact, bare silica particles formed aggregates easily, resulting in gel formation at a small amount of bare silica (2-3 wt %).…”
Section: Gelation Of Il With Polymers and Nanoparticlesmentioning
confidence: 99%
“…In addition, hydrophobic nanoparticles were prepared by grafting poly(MMA) chains on the particle surfaces to understand the peculiar colloidal stability. [84][85][86] The colloidal interaction was investigated using the Derjaguin-Landau-Verway-Overbeek (DLVO) theory, from which it was concluded that bare silica particles cannot be stabilized in ILs. In fact, bare silica particles formed aggregates easily, resulting in gel formation at a small amount of bare silica (2-3 wt %).…”
Section: Gelation Of Il With Polymers and Nanoparticlesmentioning
confidence: 99%
“…12 Few other reports include viscosity measurements of ILs containing small amounts of nanoparticles. [29][30] IL-functionalized multi walled carbon nanotubes have been prepared and added to a neat IL and the viscosity of the resulting nanofluid was lower than the neat IL due to the lubricating properties of carbon nanotubes. 31 The effect of various weight loadings of Al 2 O 3 spheres on the viscosity of the NEIL at elevated temperatures was measured and is reported in Figure 5.…”
Section: Viscositymentioning
confidence: 99%
“…In cases where drying or vacuum treatment steps are employed to remove volatile co-solvents or other gelation reaction byproducts, total gel formation times can be several days. Common ionogel fabrication methods include: use of a co-solvent to blend in a polymer support, 3,5,[20][21][22] initiation of a spontaneous sol-gel reaction to produce an inorganic support, [23][24][25][26] stirring in an assembly of fumed silica particles, [27][28][29] and either UV-initiated [30][31][32][33] or thermally-initiated [34][35][36][37][38][39][40] polymerization/crosslinking of a reactive monomer inside the ionic liquid. Additionally, chemical vapor deposition and alternative polymerization strategies that require on the order of minutes have been reported.…”
mentioning
confidence: 99%